A new metriacanthosaurid theropod dinosaur from the Middle Jurassic of Yunnan Province, China - Yi Zou; Li Chen; Tao Wang; Guo-Fu Wang; Wei-Gang Zhang; Xiao-Qin Zhang; Zhen-Ji Wang; Xiao-Chun Wu; Hai-Lu You (PeerJ)
Metriacanthosaurid theropods represent a basal-branching lineage of tetanurans. Members of this clade are mainly medium to large-sized and lived in Laurasia during the Middle Jurassic to the Early Cretaceous. In this clade, Sinraptor dongi, Sinraptor hepingensis, and Yangchuanosarus shangyouensis from the Late Jurassic are well represented by the nearly complete specimens, but the incompleteness of Middle Jurassic taxa hinders our knowledge of the origin and early evolution of Metriacanthosauridae. This paper describes a new genus and species of metriacanthosaurids, Yuanmouraptor jinshajiangensis gen. et sp. nov, from the Middle Jurassic Zhanghe Formation of Yunnan Province, China. The new taxon is represented by a cranium and the anterior section of the vertebral column including the complete cervical series and the first dorsal vertebra. Yuanmouraptor jinshajiangensis can be diagnosed based on the following autapomorphies: the anterior process of postorbital sheet-shaped and keeping consistent depth; ventral ramus of postorbital bearing a laterally twisted trough running along its lateral surface; ventral surface of axial intercentrum parallel with that of axial centrum; discontinuity of inclination on anterodorsal margin of the third and fourth cervical vertebrae; strongly posteriorly elongated epipophyses of anterior cervical vertebrae; deeply excavated pneumatic foramina on the third cervical vertebra; sheet-shaped and subrectangular neural spines of posterior cervical vertebrae. Phylogenetic analysis recovers Yuanmouraptor as the most basal-branching member within Metriacanthosauridae and provides a new alternative phylogenetic topology of non-coelurosaurian tetanurans.